Management Strategy for the Erau Festival as a Cultural Tourism Attraction in the Kutai Kartanegara Ing Martadipura Sultanate, East Kalimantan - Diece Christy Aliesa; Yohanes Kristianto; Putu Sucita Yanthy (Cita Konsultindo Research Center, 2024)
The festival was part of event management that aimed to preserve local culture and enhance the economic growth of tourism destinations. The management of festivals in the context of cultural tourism had become a strategic approach in the development of culturally-based tourism destinations. The Erau Festival, as a cultural heritage of the Kutai Kartanegara Sultanate, attracted considerable attention from tourists. Thus, it had significant prospects for being developed into a cultural tourism attraction. The aim of the research was to analyse the potential for cultural tourism, the role of stakeholders, and the formulation of alternative management strategies for the future. The method used was qualitative with a descriptive approach. Its main focus was to provide an in-depth understanding of the phenomenon under study. Data was collected through triangulation. Observations were carried out in a participatory manner, with the researcher involved in the Erau Festival and observed the ongoing interactions. In-depth interviews were conducted with key informants, including academics, businessmen, government, community, and media. The researcher also documented the Erau Festival activities to strengthen the research. The collected data was analysed using SWOT techniques. The findings indicated that the Erau Festival had significant cultural heritage potential but had not yet been packaged in a cultural tourism approach. Stakeholders played a role in its management, but this was limited to the local government and the Kutai Kartanegara Sultanate. Other stakeholders had not played any role at all. Based on these findings, ten alternative strategies were proposed for managing the Erau Festival to make it more effective and efficient. The implication was to develop the Erau Festival as a cultural tourism attraction to preserve local assets and enhance economic growth for the local community.